Data journalism's actors, practices and skills: A case study from Quebec. (January 2016) - Tabary, Constance; Provost, Anne-Marie; Trottier, Alexandre
This article investigates occurrences of data journalism between 2011 and 2013 in the Canadian province of Quebec in order to identify and examine its actors, data access conditions, practices and the required computer and statistical skills. We analysed six Quebec media outlets' quantification and statistical data visualization projects. We noticed a growth in the production of data journalism during the period, but this production is in general of little depth and does not lead to journalists learning new skills. One considerable barrier to the production of quality data journalism in Quebec is the lack of quality data offered by the provincial and federal government.